USING STUDENT TEAMS ACHIEVEMENT DIVISIONS TO ENHANCE STUDENTS’ ENGAGEMENT IN READING COMPREHENSION OF PROCEDURE TEXT - Warnida, Lisda; Ikhsanudin, Ikhsanudin; Regina, Regina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractStudents’ engagement impacts significantly to students’ achievement. When students are engaged in learning activity, it will be easy for them to understand the materials given by the teacher and they are able to focus on the lesson. Students’ engagemet will have a good effect to students’ self confidence, interest, and motivation. In teaching, the writer found that most of the students were not engaged in learning activity escpecially the students of IX E at MTsN 2 Pontianak that consists of thirty eight students, in  academic year 2017-2018. It could be seen from the students attitude toward the lesson. Most of the students exhibited low interest in learning. It was hard for them to focus on the teacher’s explanation. They also had low motivation and less attention. To overcome this problem, the writer chose one of the cooperative learning model namely Student Teams Achievement Division or STAD. STAD is made up of five major components: class presentation, teams, quizzes, individual improvement scores, and team recognition. This research aimed at enhancing students’ engagement in reading comprehension of procedure text. STAD can be used as an alternative method for teaching reading and it can make students more active in participating or interacting with their friends to answer the questions. In this research, the writer applied a classroom action research in three cycles. Each cycle consisted of two meetings. The data have been collected by using the observation checklist, field notes, and questionnaire. After conducting the research, there was a significant improvement on students’ reading comprehension and especially on students’ engagement in teaching learning process. According to the writer, STAD can be used as one of the alternatives to enhance students’ engagement and students’ motivation as well. By learning in a group, the students are able to improve their self confidence, their self esteem and their competences.Keywords: CAR, Cooperative Learning, Reading Comprehension, STAD.